Bidentate surface structures of glycylglycine on Si(111)7×7 by high-resolution scanning tunneling microscopy site-specific adsorption via N-H and O-H or double N-H dissociation - Chatterjee, A (Langmuir : the ACS journal of surfaces and colloids, 2012)
The early adsorption stage of glycylglycine on Si(111)7×7 surface has been studied by scanning tunneling microscopy (STM). Filled-state imaging shows that glycylglycine adsorbs dissociatively in a bidentate fashion on two adjacent Si adatoms across a dimer wall or an adatom-restatom pair, with the dissociated H atoms on neighboring restatoms. The present STM result validates our hypothesis that both bidentate configurations involving N-H and O-H dissociation and double N-H dissociation are equally probable. Our STM results further show that the relative surface concentrations of the five bidentate configurations follow a specific ordering. This suggests that N-H dissociation at a center adatom site would likely be followed by N-H dissociation at an adjacent restatom, while N-H dissociation at a corner adatom site would be succeeded by O-H dissociation at an adatom across the dimer wall. Evidently, the strong bidentate interactions also inhibit surface diffusion of the adsorbed glycylglycine fragment, and the adsorption apparently follows random sequential adsorption statistics. The random nature of adsorption is also supported by the similar relative occupancies of the center adatom and corner adatom sites, indicating that the relative reactivities of these adatom sites do not play a significant role. Our DFT computational study shows that all three bidentate (Si-)NHCH(2)CONHCH(2)COO(-Si) adatom-adatom configurations (center-center, corner-corner, center-corner) have similar adsorption energies for a double adatom-adatom pair across the dimer wall, while the (Si-)NHCH(2)CON(-Si)CH(2)COOH bidentate adatom-restatom configuration is energetically favorable. The free -CONH- and -COOH groups remaining on the respective bidentate adstructures could facilitate adsorption of the second adlayer through the formation of hydrogen bonding